THE RIGHT TO CODE AND SHARE ARMS. - BLACKMAN, JOSH (Law & Contemporary Problems, 2020)
The article describes the battle over three-dimensional (3D)-printed firearms and the First Amendment interests at stake in U.S. government attempts to regulate the Internet files that could be used to print these guns. He recounts his role as counsel for the online open-source hardware organization Defense Distributed and his challenge for free-speech advocates to support Defense Distributed.